PENGARUH PENAMBAHAN SUSU FULL KRIM PADA BERBAGAI LEVEL TERHADAP KUALITAS PRODUK HOMEMADE YOGURT YANG MENGGUNAKAN YOGURT PLAIN SEBAGAI STARTER - Goleng, Markus (Universitas Kanjuruhan Malang, 2013)
The experiment was conducted at the Laboratory of the Faculty of Animal Husbandry Kanjuruhan University of Malang, on December 6, 2013 to January 6, 2014. The purpose of this study was conducted to determine the effect of full-cream milk at various levels on pH, protein content and organoleptic quality plain yogurt. The method used in laboratory experiments with completely randomized design (RAL). With treatment and 3 respectively each treatment was repeated 3 times. The treatment is done is the addition of full-cream milk with levels of 15 grams, 20 grams and 25 grams. The variables measured were pH, protein content and organoleptic quality. The result showed that the use of full-cream milk levels using plain yogurt as a starter that does not give effect significantly (P >0.05) on the pH of yogurt and organoleptic quality. Based on the analysis of variance showed that the use of full-cream milk levels using plain yogurt as a starter gives a significant influence (P<0.01) in to protein content of yogurt. The conclusion that there is a very real effect on the level of the addition of full-cream milk at various levels provide the highest protein content of 4.96% homemade yogurt products that use plain yogurt as a starter. There was no effect of the addition of full-cream milk at various levels on the pH (degree of acidity) and organoleptic quality homemade yogurt products that use plain yogurt as a starter.Keywords: Full cream, Starter, Yogurt, Homemade Yogurt, Yogurt Plain, Quality